Welfare to Work in the US: A Model for Germany? - Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2001)
Social assistance in Germany reduces the incentive to work. TheU. S. Welfare to Work Programme tries to avoid such disincentives. It consists essentially of two elements: the Earned Income Tax Credit (EITC) for employees in low wage occupations and a Workfare model. The EITC and the Workfare model as implemented in the State of Wisconsin are described andanalysed. Conclusions for welfare reform in Germany are drawn.
Keywords: 330